SYNTHESIS OF PROPERTIES N-METHYL-2-(PYRID-4-YL)-3,4-FULLEROPYRROLIDINE - S.D. Fazylov,; O.A. Nurkenov,; A.E. Arinova,; T.M. Seilkhanov,; A.M. Gazaliev,; M.K. Ibraev,; A.S. Fazylov, (Academic Scientific Journal of Chemistry, 2020)
The article is devoted to the reactions of [2+3] cycloaddition of pyridine-4-aldehyde to fullerene C60, as well as to the preparation of its water-soluble from of the resulting reaction product N-methyl-2-(pyrid-4-yl)-3,4- fulleropyrrolidine. A literature review of organic compounds containing the pyrrolidine cycle was carried out. It is noted that such compounds have a wide spectrum of biological activity and are part of many drugs of both natural and synthetic origin. In this regard, an interesting “pharmacophore” group is the pyridine cycle, which is part of about 5% of all known drugs. The reaction of pyridin-4-aldehyde with fullerene C60 was carried out in the presence of sarcosine under the conditions of the Prato reaction. The reaction mechanism of 1,2-dipolar cycloaddition, leading to fulleropyrrolidine, is described. The watersoluble complex fulleropyrrolidinas with poly-N-vinylpyrrolidone was obtained. The structures of the synthesized compounds were studied by IR, UV, 1 H and 13C NMR spectroscopy, as well as by the date of two-dimensional spectra of COSY (1H-1H) and HMQC (1 H-13H). The values of chemical shifts, multiplicity and integrated intensity of 1 H and 13C NMR signals in one-dimensional NMR spectra were determined. Using spectra in the formats COSY (1H-1H) and HMQC (1H-13C) homo- and heteronuclear interaction were established, confirming the structure of the studied compounds